A Study in to the Dynamic Behavior of Packed Distillation Column - F. Tobia, Ittehad; M. Putrus, Karima; M. Hameed, Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
The study of the dynamic behavior of packed distillation column was studied by frequency response analysis using Matlab program. A packed distillation column (80 mm diameter) (2000 mm height) filled with glass packing (Raschig Rings 10mm), packing height (1500 mm) has been modified for separation of methanol-water mixture (60 vol%). The column dynamic behavior was studied experimentally under different step changes in, feed rate (±30%), reflux rate (±22%), and reboiler heat duty (±150%), the top and bottom concentration of methanol were measured. A frequency response analysis for the above step response was carried out using Bode diagram, the log modulus and the phase angle were used to analyze the process model. A Matlab program was used to study the dynamic model for continuous packed distillation to predict the transient response to a step change in feed rate, reflux rate and reboiler heat duty. It also used to find the frequency response analysis using experimental data and the results were compared with A RX(Auto Recursive) model, then the plot of Bode diagram was carried. Finally the transfer function to step change in feed rate was found and represented by second order as shown in equation below. For reflux rate change, it was found that for the top concentration, it can be represented by first order (lead - lag system). Finally a comparison between the experimental and theoretical response curves were made, it was found that the model obtained from Matlab program (Bode diagram) gave a good agreement with experimental data while the model obtained using process reaction curve method shows a deviation between the theoretical and experimental data.